Trauma-focused cognitive behavioural therapy for young children: clinical considerations. (15th December 2017) - Pollio, Elisabeth; Deblinger, Esther
ABSTRACT: Trauma-focused Cognitive Behavioural Therapy (TF-CBT) has been utilized with children of a wide age range and with diverse trauma experiences. This article will focus on the application of TF-CBT to young children. After presenting an overview of the model, challenges and developmentally-sensitive and creative strategies for engaging young children and their caregivers in TF-CBT PRACTICE components will be highlighted. A brief review of the strong empirical support for TF-CBT will then be provided.